Assessment of waste generation, composition and revenue loss estimation due to floatable riverine litter at Log Boom Sungai Pinang, Klang, Malaysia - Azmar, Noor Azwani; Abd Manaf, Latifah (Malaysian Institute Of Planners, 2024)
The presence of floatable riverine litter poses a significant environmental challenge, impacting both aquatic ecosystems and local economies. The purpose of this study is to quantify waste generation and composition based on two different seasons and estimate revenue loss from floatable litter at the log boom in Sungai Pinang. Using systematic waste sampling and analysis techniques, we categorised and measured the types and volumes of waste collected over a specified period. The data revealed substantial quantities of plastic, organic matter, and miscellaneous debris. To estimate the economic impact, we employed a revenue loss model that considers cleanup costs, damage to local fisheries, and the tourism sector. Our findings indicate that the accumulation of floatable riverine litter results in considerable economic losses annually. The study highlights the urgent need for effective waste management strategies and policies to mitigate the negative impacts of riverine litter on both the environment and the local economy.